Effects of Diluents and Cryoprotectants on Native Chicken Sperm Motility - Asmarawati, Widya (2014)
This research conducted to determine the influence of various cryoprotectants and diluents on post-thawing semen quality. Two diluent used were buffer phosphate (BP) and egg-yolk buffer phosphate (EYBP). Three cryoprotectants added to the diluents were glycerol (G), dimethyl formamide (DMF) and dimethyl sulfoxide (DMSO). Semen were collected from 4 males chicken aged 1 year to 1.5 years. After examined, 2 different diluents and 3 different cryoprotectants were adding into polled semen that was devided into 6 different treatment tubes (BP+G 7%, BP+DMF7%, BP+DMSO7%, EYBP+G 7%, EYBP+DMF7%, and EYBP+DMSO7%), then prosessed to be frozen with slow freezing method. Motility before dan after equilibration were examined. Frozen semen was stored at temperature -196 °C for a week, then thawed and its motility were examined. Fresh sperm quality were analyzed with mean and standard deviation, whereas data of motility before equilibration, after equilibration, and post-thawing were analyzed by analysis of variance using completely randomized design factorial 2 x 3. The result showed that diluents treatment gave significant differences (P<0.05) on sperm motility after equilibration and post-thawing, but not gave significant differences on sperm motility before equilibration. Cryoprotectant treatments gave significant differences (P<0.01) on sperm motility before equilibration and after equilibration, but not gave significant differences on post-thawing sperm motility. It can be concluded that DMF adding into EYBP diluents gave highest post-thawing sperm motility.